High temperature tribological properties of polybenzimidazole (PBI). (16th October 2017) - Jean-Fulcrand, Annelise; Masen, Marc A.; Bremner, Tim; Wong, Janet S.S.
Abstract: Polybenzimidazole (PBI) is a high performance polymer that can potentially replace metal components in some high temperature conditions where lubrication is challenging or impossible. Yet most characterisations so far have been conducted at relatively low temperatures. In this work, the tribological properties of PBI were examined with a steel ball-PBI disc contact at 280 °C under high load and high sliding speed conditions. The dry friction coefficient is relatively low and decreases modestly with increasing applied load. Surface analysis shows that PBI transfer layers are responsible for the low friction observed. In-situ contact temperature measurements were performed to provide for the first time direct links between the morphology and distribution of the transfer layer, and the temperature distribution in the contact. The results show that high pressure and high temperature in heavily loaded contacts promote the removal and the subsequent regeneration of a transfer layer, resulting in a very thin transfer layer on the steel counterface. FeOOH is formed in the contact at high loads, instead of Fe2 O3 . This may affect the adhesion between PBI and the counterface and thus influence the transfer layer formation process. To control PBI wear, contact temperature management will be crucial. Graphical abstract: Highlights: PBI has load independent friction but wear severity depends on load at 280 °C. PBI transfer film on steel controls friction and its morphology depends on load. Contact temperature distribution governs transfer film distribution in contact. High applied load causes high contact temperature and leads to high PBI wear. To use PBI at severe rubbing conditions, contact temperature needs to be managed.